MEMBEDAH KESEHATAN FINANSIAL BUMDES SUKSES BERSAMA SUGIHWARAS: PERSPEKTIF RASIO KEUANGAN - Nur Amiril; Husnayetti; Junarti; Gusneli (Prodi Akuntansi FEB UNITOMO, 2024)
This study analyzes the financial wellness of Badan Usaha Milik Desa (BUMDes) Sukses Bersama Sugihwaras for the 2021-2022 period, given the importance of a deep understanding of BUMDes' financial performance. The aim is to evaluate the financial dynamics of the BUMDes comprehensively. The method used is financial ratio analysis, covering liquidity, solvency, profitability, and efficiency. Results show significant liquidity improvements, capital structure strengthening, and asset utilization efficiency. Despite slight decreases in ROE and ROA, the BUMDes maintained good profitability with an increased Net Interest Margin (NIM). In conclusion, BUMDes Sukses Bersama Sugihwaras demonstrates overall positive financial performance, providing valuable insights for future strategic decision-making.